The Impact of Public Relations, Personal Selling, and Brand Image on the Decision to Join: An In-Depth Analysis - Mulyanto, John Calvin; R, Ike Kusdyah; Handoko, Yunus (Al-Qalam Institue, 2025)
This study investigates the influence of Public Relations, Personal Selling, and Brand Image on customer decisions to join YDK Group Indonesia in Surabaya-Bali. Utilizing a quantitative approach, the research sampled 40 customers through saturated sampling and employed multiple linear regression analysis with SPSS version 25. The results indicate that Public Relations and Personal Selling did not significantly affect customers' decisions, contrary to previous studies. However, Brand Image was found to have a significant positive impact, confirming its crucial role in customer decision-making. The simultaneous effect of Public Relations, Personal Selling, and Brand Image on customer decisions was also significant, marking this research as the first to demonstrate the combined influence of these factors in the context of non-sharia life insurance. The findings highlight the importance of a comprehensive approach, integrating these variables, to enhance customer acquisition and retention strategies. This research contributes to the literature by providing actionable insights for insurance companies, especially new and emerging players, in shaping effective customer engagement strategies and building trust in a competitive market.